Skill acquisition for sports performance - Baricevic, Thomas; Marshall, Jared; Moloney, Cameron; Video Education Australasia (Bendigo, Vic. : Video Education Australasia, 2010)
"The ultimate goal of any aspiring athlete is to execute skills with form and efficiency. This program provides a detailed theoretical understanding of how skills are developed and honed to an elite level. We learn the difference between skills and abilities, explore types of skills, step through the three stages of skill acquisition,and discuss how everyone learns at a different rate. We also discuss internal and external factors that affect performance and learn useful techniques to evaluate performance. All of this theory is underpinned throughout the program be real-life examples and expert advice from head coach Gary Wagner and sports psychologist Shayne Hanks." -- Case slip
Director, Jared Marshall ; written by Cameron Moloney ; producer, Thomas Baricevic.
Narration, Chanta Bui Viet.
Keywords: Physical education and training; Physical fitness; Sports -- Physiological aspects; Sports -- Psychological aspects